Implication of internet of things (IoT) on organisational performance for SMEs in emerging economies – a systematic review - Muridzi, Gibson (Technology audit and production reserves, 2023)
The object of this research is the implementation of Internet of Things (IoT) and its effect on organizational performance for Small and Medium Enterprises (SMEs) in emerging economies. SMEs in emerging economies are faced with low level of performance due to technological constraint, inadequate skilled human resource, lower entrepreneurial capabilities and management systems, the deficiency of available information, inadequate use of Information Technology, poor quality products and lack of strategic long-term plans. Systematic literature reviews approach was used to discover, assess and synthesize findings of all relevant individual research on fourth industrial revolution (4IR), IoT, organization performance and SMEs topics. 461 articles were found, and 60 articles were used as sample of this study. Findings of this study established that implementation of IoT positively affects performance for SMEs in emerging economies. Results also shows that financial, technological, and operational risks are major risks faced by SMEs in implementing IoT technologies in emerging economies. The essence of the results is to contribute to current body of knowledge by giving interesting insights in the form of a framework on how IoT technologies can be applied in enhancing SMEs performance in emerging economies. This is achieved by making SMEs aware of its potential benefit by providing some knowledge on securing financial resources, and ability to analyse external environment, and to shed more light on the benefits and opportunities that these new tools offer and how it can subsequently improve organization performance for SMEs. Most articles used systematic literature review were from developed economies as there was limited literature which speaks about IoT and SMEs performance in emerging economies. The study therefore focused on IoT and how it can improve SMEs’ organizational performance in emerging economies.